2015
DOI: 10.1093/nar/gkv914
|View full text |Cite
|
Sign up to set email alerts
|

MCM ring hexamerization is a prerequisite for DNA-binding

Abstract: The hexameric Minichromosome Maintenance (MCM) protein complex forms a ring that unwinds DNA at the replication fork in eukaryotes and archaea. Our recent crystal structure of an archaeal MCM N-terminal domain bound to single-stranded DNA (ssDNA) revealed ssDNA associating across tight subunit interfaces but not at the loose interfaces, indicating that DNA-binding is governed not only by the DNA-binding residues of the subunits (MCM ssDNA-binding motif, MSSB) but also by the relative orientation of the subunit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 69 publications
(97 reference statements)
0
5
0
Order By: Relevance
“…The MCM complex is a hexameric ring helicase that separates parental DNA strands at the replication fork in eukaryotes and archaea. The X-ray crystal structures of archaeal MCM proteins have revealed overall architectural features that are highly conserved in both archaea and eukaryotes [ 3 , 41 , 81 85 ]. All MCM hexamers assemble with a two-tiered architecture with a larger C-terminal AAA+ tier and an N-terminal tier (Figures 3(a) and 3(d) ) [ 41 , 51 , 86 89 ].…”
Section: Archaeal Aaa+ Hexamers Share Common Structural and Functimentioning
confidence: 99%
“…The MCM complex is a hexameric ring helicase that separates parental DNA strands at the replication fork in eukaryotes and archaea. The X-ray crystal structures of archaeal MCM proteins have revealed overall architectural features that are highly conserved in both archaea and eukaryotes [ 3 , 41 , 81 85 ]. All MCM hexamers assemble with a two-tiered architecture with a larger C-terminal AAA+ tier and an N-terminal tier (Figures 3(a) and 3(d) ) [ 41 , 51 , 86 89 ].…”
Section: Archaeal Aaa+ Hexamers Share Common Structural and Functimentioning
confidence: 99%
“…MCM3, as an important component of the MCM2–7 complex, plays an important role in the cell cycle and DNA replication [38] . The hexameric proteins formed by MCM2-MCM7, which unwind DNA, are normally expressed during the cell cycle, and it has been reported that the MCM2–7 loop alone could unwinds double-stranded DNA in vitro in several archaea [ 39 , 40 ]. However, even a minor reduction in the MCM pool can negatively affect the integrity of the genome, as shown by DNA fragmentation, micronuclei formation, and genomic instability [41] .…”
Section: Discussionmentioning
confidence: 99%
“…The peripheral helical bundle interacts with the OB fraction via a slight linker promoting the interaction with DNA 58 . The observation indicated that a helical bundle might be essential for protein–protein interplay and protein–DNA interactions during the initiation step.…”
Section: Evolution Of the Core Replication Proteinsmentioning
confidence: 95%
“…56,57 The peripheral helical bundle interacts with the OB fraction via a slight linker promoting the interaction with DNA. 58 The observation indicated that a helical bundle might be essential for protein-protein interplay and protein-DNA interactions during the initiation step. However, molecular mechanics studies presented that deleting a helical bundle exerts a limited influence on MCM function.…”
Section: Cmg Complexmentioning
confidence: 99%